Stosunki polsko-rosyjskie w czasie rządów Prawa i Sprawiedliwości (2005-2007)= Polish-Russian relations during the rule of Law and Justice (2005-2007) - Hozakowska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Polish-Russian relations for centuries were marked by conflict. Polish political transformation in 1989 meant that our country had entered a new stage of building our independence from our big neighbor. Problems in these relations were due to historical reasons, disputes regarding energy and Polish support for the democratic transition in post-Soviet republics. In 2005 the right-wing Law and Justice party (PiS), whose leaders were determined to run tough policy towards the Russian Federation, won the parliamentary election.
Keywords: stosunki polsko-rosyjskie; Nord Stream; tarcza antyrakietowa; Prawo i Sprawiedliwość (PiS); Polish-Russian relations; Missile Defence; Law and Justice party (PiS)